Dr. Elena Pozdnikina — Deep Plane Facelift — Saint Petersburg - Pozdnikina, Elena (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Elena Pozdnikina, practicing in Saint Petersburg, Russia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003104; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; russia; saint petersburg